Therapeutic effects of forest bathing on older adult patients with essential hypertension: evidence from a subtropical evergreen broad-leaved forest - Li, Aibo; Liu, Yu; Qian, Haiyuan; Sun, Kun; Zhao, Ziqing; Uehara, Iwao; Wang, Guofu; Zhou, Benzhi (Frontiers in Public Health, 2025)
IntroductionForest bathing (Shinrin-Yoku) has gained growing attention in medical and therapeutic tourism research due to its potential benefits in managing chronic diseases, such as hypertension. This empirical study examined the therapeutic effects of forest bathing on older adult patients with essential hypertension.MethodsA total of 36 participants were randomly assigned to either a forest environment (experimental group, n = 24) or an urban setting (control group, n = 12) for a three-day, two-night intervention. To minimize potential confounding factors, both groups followed identical dietary regimens, leisure activities, and sleep schedules throughout the intervention. Physiological and psychological assessments, including vital signs, inflammatory markers, heart rate variability (HRV), and mood states, were conducted at baseline and post-intervention.ResultsThe results indicated that systolic blood pressure (SBP), diastolic blood pressure (DBP), and high-sensitivity C-reactive protein (hs-CRP) levels were significantly lower in the experimental group compared to the control group (p < 0.05). Frequency domain parameters of HRV, specifically LF and the LF/HF ratio, significantly increased in the experimental group (p < 0.05). Additionally, psychological assessments revealed that participants exposed to the experimental group had significantly better emotional well-being. Specifically, tension-anxiety scores decreased significantly, while vigor-activity scores increased (p < 0.05).DiscussionThese findings suggest that forest bathing can serve as an effective non-pharmacological intervention for reducing blood pressure, improving autonomic function and mental health among older adult patients with essential hypertension. This study provides empirical evidence supporting the therapeutic potential of forest environments, particularly subtropical broad-leaved evergreen forests, in the integrated management of cardiovascular and mental health.